2014
DOI: 10.4102/sajpsychiatry.v20i2.528
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed metabolic syndrome and other adverse effects among clozapine users of Xhosa descent

Abstract: Background. Clozapine use is known to be associated with significant side-effects, including prolongation of the QT-interval, agranulocytosis and metabolic syndrome. However, few data exist on the prevalence of clozapine side-effects in patients of Xhosa descent. Objective. To gather data from Xhosa patients with schizophrenia to establish the prevalence of clozapine side-effects in this population. Methods. Twenty-nine Xhosa patients with schizophrenia (as per the Diagnostic and Statistical Manual of Mental D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
2
6
0
2
Order By: Relevance
“…For our study, we extracted data from the Clozaril-alone arm of the crossover study [ 62 ], as the prevalence of constipation within both arms over the study was unclear and this arm provided more data. Additionally, eight prospective studies [ 17 , 49 , 58 , 61 , 65 , 66 , 67 , 68 ], six retrospective cohort studies [ 48 , 50 , 56 , 57 , 59 , 69 ], and four cross-sectional studies [ 24 , 70 , 71 , 72 ] were included. Of the 21 studies that reported on the prevalence rate of clozapine-associated constipation, one was carried out across more than one geographical region [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For our study, we extracted data from the Clozaril-alone arm of the crossover study [ 62 ], as the prevalence of constipation within both arms over the study was unclear and this arm provided more data. Additionally, eight prospective studies [ 17 , 49 , 58 , 61 , 65 , 66 , 67 , 68 ], six retrospective cohort studies [ 48 , 50 , 56 , 57 , 59 , 69 ], and four cross-sectional studies [ 24 , 70 , 71 , 72 ] were included. Of the 21 studies that reported on the prevalence rate of clozapine-associated constipation, one was carried out across more than one geographical region [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 21 studies that reported on the prevalence rate of clozapine-associated constipation, one was carried out across more than one geographical region [ 63 ]. Five studies were carried out in Europe [ 24 , 57 , 63 , 68 , 70 ], seven in North America [ 17 , 45 , 50 , 59 , 60 , 63 , 64 , 65 , 72 ], six in Asia [ 49 , 56 , 58 , 61 , 63 , 66 ], two in Africa [ 62 , 71 ], one in the Middle East [ 48 ], and one in Oceania [ 69 ]. Nine studies were conducted in in-patient settings ( n = 395) [ 17 , 48 , 49 , 50 , 58 , 59 , 60 , 61 , 65 ], 10 involved outpatients ( n = 627) [ 24 , 56 , 57 , 62 , 66 , 68 , 69 , 70 , 71 , 72 ], and two included patients from mixed settings ( n = 56) [ 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data for South Africa are limited to three studies [ 15 17 ]. A study of 84 long term in patients that included patients with cognitive and personality disorders reported a MetS prevalence of 32% [ 15 ] while the other two reported on the prevalence of MetS in patients taking a single antipsychotic [ 16 , 17 ]. From population studies in South Africa, the reported prevalence of MetS is 22.1% in rural [ 18 ] and 31.7% in urban black South African communities [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…O índice de massa corporal (IMC) é, indiscutivelmente, o indicador antropomé-trico mais utilizado mundialmente, sendo extremamente útil na prática clínica para determinar a obesidade. Esse índice pode ser utilizado como uma medida de rastreamento de SM em pacientes que possuem esquizofrenia refratária e utilizam clozapina (28,30). Estudo que comparou as alterações metabó-licas possivelmente relacionadas ao uso de antipsicóticos mostrou que 52,3% dos indivíduos estavam com sobrepeso e indicou que aqueles que possuíam esquizofrenia refratá-ria apresentaram as maiores taxas (31).…”
Section: Resultsunclassified